1998
DOI: 10.1002/(sici)1098-2256(1998)13:1<61::aid-tox4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variabilities of the concentrations of intra- and extracellular microcystin and toxicMicrocystis species in a hypertrophic lake, Lake Suwa, Japan (1991-1994)

Abstract: Temporal variability in the concentration of toxic heptapeptide microcystin was studied ( ) ( ) during the warm season of four years 1991 -1994 in a hypertrophic lake Lake Suwa in central ( ) ( Honshu, Japan. Lake water samples ca. 5 L were filtered to separate intracellular microcystin cell ) ( ) fraction from extracellular microcystin filtered lake water fraction . These fractions were analyzed to measure the total quantity of microcystin in lake water. Total amounts of extra-and intracellular microcystin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 32 publications
10
98
0
Order By: Relevance
“…MCs were prepared and measured as previously described [14] with some improvements. Briefly, the materials were extracted three times with 10 mL of 75% methanol (v/v) for 3 h at 4 .…”
Section: Toxinmentioning
confidence: 99%
“…MCs were prepared and measured as previously described [14] with some improvements. Briefly, the materials were extracted three times with 10 mL of 75% methanol (v/v) for 3 h at 4 .…”
Section: Toxinmentioning
confidence: 99%
“…The samples were centrifuged at 12 000g for 10 min, and the supernatant was used to determine the concentration of MC-RR. MCs samples were prepared according to the method of Park and Lwami (1998) with minor modifications. 1-ml supernatant of the samples was applied to a C18 reversed phase cartridge (0.5 g), which had been preconditioned by washing with 10-ml 100% methanol and 10-ml distilled water.…”
Section: Concentration Determination Of Mc-rr In the Mediummentioning
confidence: 99%
“…Recovery experiments were performed in sixplicate spiked water as described previously (Park and Lwami, 1998): 1 ml 1 mg/ml of purified MC-RR was applied to 0.5 g C18 reversed phase cartridge, and the column was washed and eluted according to the above method of MC-RR samples preparation. The recovery of the analytical method was calculated.…”
Section: Concentration Determination Of Mc-rr In the Mediummentioning
confidence: 99%
“…It was reported that the content of MC-RR in the isolated strains of M. viridis and M. aeruginosa from Dianchi Lake were higher than that of MC-LR. [16,17] Park et al [18] observed that the content of MC-RR in collected cyanobacterial cells from Lake Suwa in Japan was much higher than that of MC-LR. Here a MC-LR rather than MC-RR producing strain M. aeruginosa DC-1 was isolated from the Dianchi Lake of China.…”
Section: Introductionmentioning
confidence: 99%